2009
DOI: 10.1002/aic.11793
|View full text |Cite
|
Sign up to set email alerts
|

Microwave regeneration of zeolites in a 1 meter column

Abstract: Although sorption is a common method of removing volatile organic compounds (VOC's) from processes, the adsorbent must be regenerated to repeat the process. The use of microwaves to regenerate the bed of adsorbent can be more efficient than conventional heating methods. Desorption of methanol from a silicalite zeolite was studied by the use of microwaves in cylindrical column. Temperature probes at five axial and three radial positions monitored the temperature profile in time. A significant amount of microwav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…The desorption process can be accomplished quickly with the help of using high microwave power or high flow rates. 241 Other industrial applications include microwave heating of a high volatile bituminous coal for rapid coke making 240 and pyrolysis of oil shale to enhance oil yield and oil quality by yielding oil containing less sulfur and nitrogen. 242 Use of microwave energy in mineral processing brings considerable benefits by reducing energy consumption and environmental pollution.…”
Section: Glass and Mineral Processingmentioning
confidence: 99%
“…The desorption process can be accomplished quickly with the help of using high microwave power or high flow rates. 241 Other industrial applications include microwave heating of a high volatile bituminous coal for rapid coke making 240 and pyrolysis of oil shale to enhance oil yield and oil quality by yielding oil containing less sulfur and nitrogen. 242 Use of microwave energy in mineral processing brings considerable benefits by reducing energy consumption and environmental pollution.…”
Section: Glass and Mineral Processingmentioning
confidence: 99%
“…While the electric field is often considered homogeneously distributed in small cavities, microwave propagation in an industrial setting has to be taken into account and combined with the chemical and physical transformations of the process. A recent work on methanol desorption from a zeolite in a 1 m waveguide column [10] demonstrates the feasibility of this process. It also studies the instantaneous and transitory behaviour of temperature and the propagation of microwave energy.…”
Section: Introductionmentioning
confidence: 95%
“…Meier et al [7] reported on microwave regeneration of silicalite zeolite from methanol in a circular waveguide, being also the 1-m desorption column. A stubbed tuner was utilized to minimize reflections of microwaves at the edges of the adsorbent bed, as these places were recognized being mostly responsible for reflections in the setup.…”
Section: Introductionmentioning
confidence: 99%